An alternative pricing system through Bayesian estimates and method of moments in a bonus-malus framework for the Ghanaian auto insurance market - Azaare Jacob; Zhao Wu (Journal of Risk and Financial Management, 2020)
This paper examines the current No-Claim Discount (NCD) system used in Ghana's auto insurance market as inefficient and outmoded and, therefore, proposes an alternative optimal Bonus-Malus System (BMS) intended to meet the present market conditions and demand. It appears that the existing BMS fails to acknowledge the frequency and severity of policyholders' claims in its design. We minimized the auto insurance portfolios' risk through Bayesian estimation and found that the risk is well fitted by gamma, with the claim distribution modeled by the negative binomial law with the expected number of claims (a priori) as 14%. The models presented in this paper recognize the longevity of accident-free driving and fully reward higher discounts to policyholders from the second year when the true characteristics of the hidden risks posed to the pool have been ascertained. The BMS finally constructed using the net premium principle is very optimal and has reasonable punishment and rewards for both good and bad drivers, which could also be useful in other developing economies.
Keywords: 330; auto insurance; Bayesian estimation; bonus-malus system; Ghana; Markovian process; negative binomial distribution